Legal Pluralism in Environmental Management: Evidence from Bali, Indonesia - Aldyan, Arsyad; Aldyan, Rizal Akbar; Asmanda, Kartika Asmanda Putri; Alasttal, Abdelrahman Alasttal (Journal of Law, Environmental and Justice, 2025)
This study explores the practice of legal pluralism in environmental governance through an in-depth analysis of customary law integration in Bali, Indonesia. As a province that maintains strong Indigenous legal traditions, Bali presents a unique setting where "awig-awig" (customary regulations), "subak" (irrigation institutions), and traditional villages actively contribute to natural resource management and ecological protection. The purpose of this research is to examine how these indigenous legal institutions operate alongside state environmental laws and to assess the normative and institutional synergies or tensions that arise. Employing a normative juridical method, this study analyzes constitutional provisions, statutory environmental regulations, and regional laws while integrating case illustrations from Penglipuran, Tenganan, and Ubud villages. The findings indicate that community-based enforcement mechanisms grounded in local norms and social sanctions provide resilient and context-specific approaches to sustainability. However, the coexistence of customary and statutory systems also exposes challenges related to authority fragmentation, legal uncertainty, and policy misalignment. The study concludes that enhancing the legal status of indigenous institutions and developing cooperative governance frameworks are essential steps toward achieving inclusive, adaptive, and culturally embedded environmental management. These findings contribute to the growing global discourse on legal pluralism and support the integration of Indigenous Ecological Knowledge (IEK) within national and international environmental agendas.